GE_GERICHTE C/26526/2010 vom 7. Februar 2014 - GE Cour de justice (2014)
CONTRAT D'ENTREPRISE; CONTRE-PRESTATION; PAIEMENT; EXÉCUTION PAR SUBSTITUTION(SANCTION); RÉSILIATION; VOL(DROIT PÉNAL) | CO.366.2